The DETERMINATION OF THE RHEOLOGICAL CHARACTERISTICS OF SOME VARIETIES OF NEW RICE FOR AFRICA (NERICA) RELEVANT TO ITS PROCESSING: DETERMINATION OF THE RHEOLOGICAL CHARACTERISTICS OF SOME VARIETIES OF NEW RICE FOR AFRICA (NERICA) RELEVANT TO ITS PROCESSING - Chukwuka, Eze Paul (Journal on Processing and Energy in Agriculture, 2022)
The pasting properties of some NERICA (New Rice for Africa) varieties were determined using the rapid visco-analytical machine (RVA). The studied varieties include FARO 44, FARO 52, FARO 57, FARO 60, and FARO 61. The parameters assessed includes the pasting temperature, peak time, peak or maximum viscosity, hot paste viscosity or trough, cold paste or final viscosity, the breakdown, and the setback. Results obtained indicated that the pasting characteristics of NERICA varieties studied exhibited good pasting behavior. Results showed that peak viscosity, final viscosity, hot paste viscosity, breakdown, and setback ranged from 30.83 to 85.17 RVU; 62.21 to 167.13 RVU; 25.83 to 76.88 RVU; and 5.01 to 8.29 RVU; and 31.38 to 81.96 RVU respectively. There were significant effects of moisture content and temperature (p < 0.05) on all parameters studied. These generated results of the pasting characteristics of NERICA will be very useful in determining their suitability in food and other relevant industries.
Keywords: NERICA, rheological properties, viscosity, pasting properties, rice.